2020
DOI: 10.3390/cells9040956
|View full text |Cite
|
Sign up to set email alerts
|

Adenosine-Related Mechanisms in Non-Adenosine Receptor Drugs

Abstract: Many ligands directly target adenosine receptors (ARs). Here we review the effects of noncanonical AR drugs on adenosinergic signaling. Non-AR mechanisms include raising adenosine levels by inhibiting adenosine transport (e.g., ticagrelor, ethanol, and cannabidiol), affecting intracellular metabolic pathways (e.g., methotrexate, nicotinamide riboside, salicylate, and 5-aminoimidazole-4-carboxamide riboside), or undetermined means (e.g., acupuncture). However, other compounds bind ARs in addition to their canon… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 123 publications
(178 reference statements)
0
12
0
Order By: Relevance
“…This regimen has now been abandoned, but it has allowed us to identify multiple pathways activated by the drug chemical precursor, salicylate, which include an indirect elevation of extracellular Ado concentrations [53]. A similar indirect influence on the Ado system has been demonstrated for high doses of other NSAIDs (i.e., sulindac) and for sulfasalazine, a prodrug of 5-amino-salicylic acid acting as a DMARD [53,54].…”
Section: Drugs Targeting the Adenosine System In Autoimmune Disordersmentioning
confidence: 92%
“…This regimen has now been abandoned, but it has allowed us to identify multiple pathways activated by the drug chemical precursor, salicylate, which include an indirect elevation of extracellular Ado concentrations [53]. A similar indirect influence on the Ado system has been demonstrated for high doses of other NSAIDs (i.e., sulindac) and for sulfasalazine, a prodrug of 5-amino-salicylic acid acting as a DMARD [53,54].…”
Section: Drugs Targeting the Adenosine System In Autoimmune Disordersmentioning
confidence: 92%
“…In addition to the aforementioned receptor- dependent actions, adenosine also yields receptor- independent actions, which rely on metabolic and intracellular levels and the metabolism of adenosine ( Boison and Yegutkin, 2019 ). ADK plays a crucial role in the regulation of both extracellular and intracellular adenosine levels ( Jacobson and Reitman, 2020 ) and adenosine receptor-dependent and independent pathways, in coordination with other adenosine metabolizing enzymes ( Boison and Yegutkin, 2019 ). We will briefly review adenosine metabolism with a focus on the relationship between receptor-independent pathways of adenosine and DNA methylation in cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Novel experimental models and promising approaches may assist in answering these questions in the future. Jacobson and Reitman have sensibly called for further knock-out in vivo studies in order to support novel findings and re-evaluate some that were reported previously [214]. On the other hand, the question of data translatability from animal studies for human therapy persists.…”
Section: Perspectivesmentioning
confidence: 96%